2019
DOI: 10.11604/pamj.2019.33.125.17589
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus correlates of high grade cervical dysplasia among HIV-Infected women at a major treatment centre in Nigeria: a cross-sectional study

Abstract: IntroductionPersistent high-risk HPV (hrHPV) infection is higher among women living with HIV/AIDS thus increasing their risk for cervical cancer. We evaluated the virological and immunological correlates of cervical dysplasia in HIV-infected women.MethodsA cohort of 220 consenting women attending the antiretroviral clinic of the Federal Medical Centre, Keffi, Nigeria was tested for cervical human papilloma virus (HPV) infection using PCR. The prevalent HPV genotypes were determined by DNA sequencing. CD4+T cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
2
13
1
Order By: Relevance
“…This demonstrates the increasing prevalence of HPV with an increase in cervical intraepithelial lesions [33,35]. A prevalence of 20.7% was noted for precancerous lesions in HIV-infected women in this study which is comparable to 25% reported in Nigeria [23].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…This demonstrates the increasing prevalence of HPV with an increase in cervical intraepithelial lesions [33,35]. A prevalence of 20.7% was noted for precancerous lesions in HIV-infected women in this study which is comparable to 25% reported in Nigeria [23].…”
Section: Discussionsupporting
confidence: 79%
“…This type is associated with precancerous and cancerous lesions [39]. High HPV 35 prevalence was also recorded in Nigeria [23]. The high HPV prevalence of HPV 31 was recorded in HSIL and ASCUS in HIV-infected women in this study.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Knowing that a great majority of invasive CC are preventable thanks to refined access to high-functioning HPV testing, a routine targeted screening would significantly decrease the burden of CC among HIV(+) women. [46] HPV presence and HIV acquisition While it has been clearly showed that HIV presence is a risk factor for HPV acquisition, some researchers started to consider the opposite correlation, in which the HPV infection might have been the risk factor for HIV acquisition. It has been estimated that HIV acquisition rate is almost two times higher among HPV(+) individuals in comparison to HPV(-) counterparts.…”
Section: Screening Of Cervical Cancer Among Hiv-positive Womenmentioning
confidence: 99%